Decision support systems (DSS) for wastewater treatment plants – A review of the state of the art - Mannina, Giorgio; Rebouças, Taise Ferreira; Cosenza, Alida; Sànchez-Marrè, Miquel; Gibert, Karina (Bioresource technology, 2019)
[Display omitted] •A literature review on DSS for wastewater treatment plants is presented.•DSSs are capable of integrating several data and a multi-criteria perspective.•The development of more user-friendly and web-based DSSs is also encouraged.•Web-based DSSs could stimulate group decision-making. The use of decision support systems (DSS) allows integrating all the issues related with sustainable development in view of providing a useful support to solve multi-scenario problems. In this work an extensive review on the DSSs applied to wastewater treatment plants (WWTPs) is presented. The main aim of the work is to provide an updated compendium on DSSs in view of supporting researchers and engineers on the selection of the most suitable method to address their management/operation/design problems. Results showed that DSSs were mostly used as a comprehensive tool that is capable of integrating several data and a multi-criteria perspective in order to provide more reliable results. Only one energy-focused DSS was found in literature, while DSSs based on quality and operational issues are very often applied to site-specific conditions. Finally, it would be important to encourage the development of more user-friendly DSSs to increase general interest and usability.